DAMPAK ENVIRONMENT UNCERTAINTY TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN AKUNTANSI - Sukma Lesmana (Jurnal Riset AKuntansi dan Bisnis, 2011)
Control system is closely related to the accounting information system in terms of providing information managers need to take control of corporate decisions (Binberg and Shield, 1989; Merchant, 1981). Control system that uses accounting information and then called Simons (1987) as a control system based on accounting or accounting control system. Accounting control system will effectively improve the performance of the company if managers take into account environment uncertainty. Environment uncertainty is an external influence that organizations can affect managers in generating outcomes. Managers should be conservative when faced with uncertainty control system design environment that can facilitate the organization achieve the expected performance.